Model of presentation of the information system curricula, using XML - Vasilecas, Olegas; Lapin, Kristina (Lietuvos matematikos rinkinys, 2002)
New curricula of information systems (IS) are developed in response to the growing need of IS specialists. A joint IS curriculum is developed in MOCURIS project within Socrates/Erasmus programme. The development group was formed from teaching staff at various universities in different countries. During development the curriculum content should be presented for the project members and other users. Presentation should correspond to various user needs: viewing, updating and printing of modules content. To coordinate the project work it is expected to send SMS to the project member's phones. Study programmes are steadily changing. It is important to prevent the recurrence of themes in modules of relative subjects. Analysis is performed in a relational database. The module content from the database is generated to XML format. XML documents are transformed to PDF, HTML or SMS formats, according to user needs.